2011
DOI: 10.1007/s10512-011-9355-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyrochemical method of salvaging weapons plutonium in oxide for fabricating mixed fuel for fast reactors

Abstract: Experimental results of investigations of pyrochemical conversion of weapons plutonium into plutonium oxide for fabricating fast-reactor fuel are presented. Weapons plutonium was hydrogenized by hydrogen at 220°C, after which the plutonium hydride obtained was acidified at 550-560°C with the formation of PuO 2 . To increase fire and explosion safety of the process, a mixture of oxygen with nitrogen, helium, or argon was used or nitriding with nitrogen and oxidation of plutonium mononitride were introduced. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In addition, the prepared nitrides readily react with moisture and oxygen [8,9]. The incorporation of these impurities can have adverse effects on the structural integrity of the reactor, as high concentrations of O and C impurities might lead to internal cladding corrosion or carburization [10,11]. Moreover, it has been shown that a significant O concentration in (Pu,Zr)N leads to the segregation of PuO 2 phase [12], which complicates the reprocessing of nitride fuels, otherwise shown to be compatible with the industrially established technology [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prepared nitrides readily react with moisture and oxygen [8,9]. The incorporation of these impurities can have adverse effects on the structural integrity of the reactor, as high concentrations of O and C impurities might lead to internal cladding corrosion or carburization [10,11]. Moreover, it has been shown that a significant O concentration in (Pu,Zr)N leads to the segregation of PuO 2 phase [12], which complicates the reprocessing of nitride fuels, otherwise shown to be compatible with the industrially established technology [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%